AN ASTEROIDAL BRECCIA: THE ANATOMY OF A CLUSTER IDP - Thomas K.L.; Blanford G.E.; Clemett S.J.; Flynn G.J.; Keller L.P.; Klock W.; Maechling C.R.; McKay D.S.; Messenger S.; Nier A.O.; Schlutter D.J.; Sutton S.R.; et al. (My University, 1995)
We report results of a consortium study of a large interplanetary dust particle known as cluster L2008#5. This cluster is composed of fifty-three fragments (>5 μm in diameter) and several hundred fines (<5 μm in diameter). Fragments and some fines were characterized using a variety of chemical and mineralogical techniques including: energy dispersive X-ray analyses for bulk chemical compositions for elements carbon through nickel, transmission electron microscopy for mineralogy, noble gas measurements, synchrotron X-ray fluorescence for trace element abundances, isotopic abundances using an ion probe, trace organic abundances, and reflectance spectroscopy. Our results show that cluster L2008#5 displays strong chemical and mineralogical heterogeneity on a size scale of the individual fragments (~ 10 μm in diameter). Despite the strong heterogeneity, we believe that nearly all of the analyzed fragments were originally part of the same cluster in space.Several methods were used to estimate the degree of heating that this cluster experienced. Variations in the inferred peak temperatures experienced by different fragments suggest that a thermal gradient was maintained. The cluster as a whole was not strongly heated; it is estimated to have a low earth-encounter velocity which is consistent with origin from an object in an asteroidal orbit rather than from a comet, which would most likely have a high entry velocity.Our conclusions show that cluster L2008#5 consists of a chemically and mineralogically diverse mixture of fragments. We believe that cluster L2008#5 represents a heterogeneous breccia and that it was most likely derived from an object in an asteroidal orbit. We also present an important cautionary note for attempts to interpret individual, small-sized 10-15 μm IDPs as representative of parent bodies. It is not unique that individual building blocks of IDPs, such as discrete olivine, pyroxene, sulfide grains, regions of carbonaceous material, and other noncrystalline material, are found in several fragments; however, it is unique that these building blocks are combined in various proportions in related IDPs from one large cluster particle.